What counts as part of a game? Reconsidering skills. Issue 1 (2nd January 2018) - Torres, Cesar R.
Abstract: The first goal of this paper is to reply to a number of criticisms levied by Gunnar Breivik and Robert L. Simon against an account of sporting skills I published almost 20 years ago in which I distinguished between constitutive and restorative skills and examined their normative significance. To accomplish this goal, I first summarize my characterization and classification of skills and then detail the criticisms. After responding to the latter, and thus reconsidering and hopefully strengthening my account of skill in sport, I turn my attention to Scott Kretchmar and Tim Elcombe's inquiry into the skills involved in competitive sport. These authors claim that contesting skills demand the same respect usually accorded to testing skills. The second goal of this paper is then to explore Kretchmar and Elcombe's inquiry under the light of my reconsidered analysis of skill. I specifically advocate a plausible relationship, both in terms of their distinctive character and relative import, between testing and contesting skills and constitutive and restorative skills. In doing so, I seek to present a more comprehensive account of skill in non-competitive and competitive sport.